Heterogeneous formation of polar stratospheric clouds – Part 2: Nucleation of ice on synoptic scales - Engel, I.; Luo, B.P.; Pitts, M.C.; Poole, L.R.; Hoyle, C.R.; Grooß, J.-U.; Dörnbrack, Andreas; Peter, T. (Atmospheric Chemistry and Physics, 2013)
This paper provides compelling evidence for the importance of heterogeneous nucleation, likely on solid particles of meteoritic origin, and of small-scale temperature fluctuations, for the formation of ice particles in the Arctic stratosphere. During January 2010, ice PSCs (polar stratospheric clouds) were shown by CALIPSO (Cloud- Aerosol Lidar and Infrared Pathfinder Satellite Observations) to have occurred on a synoptic scale (1000 km dimension). CALIPSO observations also showed widespread PSCs containing NAT (nitric acid trihydrate) particles in December 2009, prior to the occurrence of synoptic-scale regions of ice PSCs during mid-January 2010.